DO CAPITAL STRUCTURE, PROFITABILITY, AND FIRM SIZE AFFECT FIRM VALUE? - Ririh Dian Pratiwi (Universitas Dian Nuswantoro Semarang, 2020)
The purpose of the research is to analyze whether there is an influence between capital structure, profitability, and firm size on firm value. The population used in this study is the LQ 45 company listed on the Indonesia Stock Exchange (IDX). A sampling of research using a purposive sampling method of determining the certain criteria with a total samples of 31 LQ 45 companies during 2014-2018. The research uses multiple linear regression to analyze the data. The results show that capital structure and profitability evaluate the value of the company. While the size of the company does not oppose the value of the company. The results of this research are expected to provide benefits for the parties, investors, and further researchers.Keywords: Firm Value; Capital Structure; Profitability Firm Size